Case Report: Immune Dysregulation Due to Toxoplasma gondii Reactivation After Allogeneic Hematopoietic Cell Transplant - Lindell, Robert B.; Wolf, Michael S.; Alcamo, Alicia M.; Silverman, Michael A.; Dulek, Daniel E.; Otto, William R.; Olson, Timothy S.; Kitko, Carrie L.; Paueksakon, Paisit; Chiotos, Kathleen (Frontiers in Pediatrics, 2021)
Disseminated toxoplasmosis is an uncommon but highly lethal cause of hyperferritinemic sepsis after hematopoietic cell transplantation (HCT). We report two cases of disseminated toxoplasmosis from two centers in critically-ill adolescents after HCT: a 19-year-old who developed fever and altered mental status on day +19 after HCT, and a 20-year-old who developed fever and diarrhea on day +52 after HCT. Both patients developed hyperferritinemia with multiple organ dysfunction syndrome and profound immune dysregulation, which progressed to death despite maximal medical therapies. Because disseminated toxoplasmosis is both treatable and challenging to diagnose, it is imperative that intensivists maintain a high index of suspicion for T. gondii infection when managing immunocompromised children, particularly in those with known positive T. gondii serologies.